Study on Aromatherapy its Therapeutic Applications and Perception of People Towards its Use in Kashmir: A Sample Survey - Syed Sabahat Ashraf; Bilal Ahmad Bhat; Aneequa Rafiquee; Nazia Fayaz Azad; Aasifa Akhter; Arshi Rafiq; Mir Misbah Sultan; Intizar Ahmad (Penerbit Hellow Pustaka, 2026)
This paper delves into the holistic practice of aromatherapy, which harnesses the therapeutic potential of aromatic compounds in essential oils derived from medicinal plants to support physical, emotional, and mental health. The study conducted in Kashmir valley traces the historical roots of aromatherapy, emphasizing its revered role in ancient civilizations, where aromatic substances were utilized for their healing properties. In this paper, a descriptive research design was used and a sample of 400 respondents (200 men and 200 women) was chosen for our study using probability technique (simple random sampling). The instrument for data collection adopted for our study was a self-designed validated questionnaire consisting of closed-ended questions. The data collected from our study was analyzed by applying descriptive as well as inferential statistical tools using the statistical package for social sciences (SPSS 21.0). The results of our study revealed that people in majority showed positive attitude towards the use of Aromatherapy. The study showed that majority of male respondents under this study revealed that the main sources of awareness towards aromatherapy were friends (40.5%), followed by family (20.5%), followed by health care professional (16.5%), followed by internet (13.5%), followed by religious scholars (9.0%). Further, main sources of awareness towards aromatherapy among female respondents were friends (31.5%), followed by family (29.5%), followed by health care professional (27.5%), followed by internet (11.5%), followed by religious scholars (7.0%). Majority of male respondents’ understudy were of the opinion that aromatherapy improves mood (31.0%), helps in better sleep (19.5%, helps in relaxation (18.5%), helps in pain relief (17.5%) and supports immune system (13.5%). Whereas, majority of female respondents were of the opinion that aromatherapy improves mood (38.0%), helps in relaxation (21.0%), helps in pain relief (17.5%), helps in better sleep (17.0% and supports immune system (11.0%). The study also highlighted the potential benefits of Aromatherapy and potential issues regarding use of aromatherapy. It was concluded that majority of respondents understudy encourage public to use aromatherapy because of its physical and mental health benefits, as well as, its cost-effectiveness and low-risk procedure for man-aging stress, anxiety, and improving quality of sleep. Finally, researchers suggest that one must consult an expert before using aromatherapy.